2014
DOI: 10.2105/ajph.2013.301607
|View full text |Cite
|
Sign up to set email alerts
|

Global Childhood Unintentional Injury Study: Multisite Surveillance Data

Abstract: Standardized ED surveillance revealed unintentional injuries are a threat to child health. The majority of events took place inside the home, challenging traditional concepts of children's safety and underscoring the need for intensified context-appropriate injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 30 publications
3
58
1
1
Order By: Relevance
“…Earlier studies from LMICs and Bangladesh have also highlighted this [6,7,10,17,18,24,25]. A multisite unintentional injury surveillance study conducted in five LMICs found that about half of all emergency department visits among children aged 0-12 years were as a result of falls [7].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Earlier studies from LMICs and Bangladesh have also highlighted this [6,7,10,17,18,24,25]. A multisite unintentional injury surveillance study conducted in five LMICs found that about half of all emergency department visits among children aged 0-12 years were as a result of falls [7].…”
Section: Discussionmentioning
confidence: 94%
“…A multisite unintentional injury surveillance study conducted in five LMICs found that about half of all emergency department visits among children aged 0-12 years were as a result of falls [7]. Again, most fall injuries are found to occur in or around the home environment, and during play [6,7,10,17,18]. This could be because children in LMICs lack designated and safe play areas [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide implementation of interventions on drowning, poisoning, falls and burns will rescue the lives of an additional 1000 childrenin a day (25).…”
Section: What Are We Expected To Do?mentioning
confidence: 99%
“…They kill approximately 830 000 children every year, and more than 95% of child injury deaths (both intentional and unintentional) occur in low-and middle-income countries (LMICs) [2]. Injuries lead to emotional trauma and financial burden for children, parents, and society [1].…”
Section: Introductionmentioning
confidence: 99%